(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The groundwater is of great potential for the fresh water in the perspective of human settlements. The quality of the groundwater for the drinking purpose is certainly the requisite for the human health. The groundwater is mostly affected by the geo-genic sources. These sources make various ions of major and minor in quantity to get dissolved in the groundwater regimes. Certainly, few trace elements are too attributable to the geo-genic sources. In usual case the dissolution does not pose any threat, but on an interference of the external or in situ driving force can disturb the fragile balance of the hydro-geochemistry. In such situations, the ionic concentrations in the groundwater pose a serious threat to the living dependable. The major ions are very obvious in the groundwater but on excess concentration can cause human health issues. The trace metals on the other hand are not typical in the groundwater but, on existence are of severe consequences to the human health. The abandonment of the contaminated groundwater sources is usually advisable but, the thoughtful monitoring of the existing groundwater sources could help the long distant goal in terms of water quality and human health. The present article is a concise review of hydro-geochemistry and human health association.